PENGARUH KEGIATAN EKSTRAKURIKULER PRAMUKA TERHADAP PEMBENTUKAN KARAKTER JUJUR SISWA DI SMA N 1 CERENTI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Rudi Agusman; Hambali '; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this study is that the scout extracurricular activities which include the goal instill honest character.However, in reality this study affect towards the honest character formation of students in SMA N 1 Cerenti. The population of this study is around 25 students by using total sampling technique. Data collection instruments is by using questionnaires with a total of 30 questions / statements, 18 questions about students' extracurricular activities scout (variable x) and 12 questions about student’s honest character (variable y). Data were analyzed by qualitative descriptive analysis which were using SPSS version 18.0. Thus the hypothesis which states